Конденсаторы для компенсации реактивной мощности по МКР-технологии: режимы работы и контроль технологии - Беспрозванных, Анна Викторовна; Лактионов, С. В. (My University, 2011)
Высокая плотность современной бытовой индуктивной нагрузки приводит к значительным потерям энергии и необходимости их возмещения за счет индивидуальных однофазных металлопленочных сухих конденсаторов. Перенапряжения приводят к частичным разрядам в газовых включениях между слоями металлизированной пленки. Контроль электрических параметров позволяет корректировать технологию изготовления самовосстанавливающихся металлопленочных конденсаторов.

High density of modern household inductive loading results in significant energy loss and brings about necessity of its compensation due to individual single-phase metallized dry capacitors. Overvoltage arising at the moment of the capacitors actuation under loading depending on parameters of the loading and the network causes partial discharges in gas inclusions between the metallized film layers. Complex control of electric parameters allows valid correction of self-restoring metallized capacitors manufacturing technique.
Capacitors for reactive power compensation via MKR-technology: operating modes and control of technology
Keywords: индуктивная нагрузка; металлопленочные конденсаторы; перенапряжения; потери энергии; inductive loading; reactive power compensation; metallized capacitors; self–restoring process; transient; overvoltage; manufacturing techniques; complex control of electric parameters